PENGARUH PELAYANAN KESEHATAN DAN PENYELENGGARAAN MAKANAN TERHADAP TINGKAT KESADARAN HIDUP SEHAT BAGI NARAPIDANA DI LEMBAGA PEMASYARAKATAN KELAS IIB SLAWI - Andi Rahmanto; Mr. Maufur (Program Studi Magister Manajemen, Universitas Pancasakti Tegal - Indonesia, 2016)
The study is done to analyze influence in partial and simultaneous between variables health services and penyenggaraan food to the level of consciousness healthy life residents under the jurisdiction of corrective services in a correctional institution class IIB slawi. Methods used is the method quantitative descriptive, by using 162 respondents. An instrument used is the questionnaire covered with a scale likert that has been tested validity and reliability, test results show the questionnaire valid and reliable/reliabel. The testing of hypotheses carried out using of linear equations multiple. The research results show that: and in partial: (1) health services berperngaruh positive on awareness healthy life; (2) the convention food have had a positive impact on awareness healthy life, (3) simultaneously shows that health services and the implementation of food have had a positive impact on awareness healthy life for prisoners in lapas class IIB slawi Password: health services, the food, awareness healthy life.